Endoprosthetic replacement of the proximal tibia for oncological conditions. (14th September 2022) - Sacchetti, Federico; Aston, Will; Pollock, Rob; Gikas, Panos; Cuomo, Pierluigi; Gerrand, Craig
Abstract : Aims: The proximal tibia (PT) is the anatomical site most frequently affected by primary bone tumours after the distal femur. Reconstruction of the PT remains challenging because of the poor soft-tissue cover and the need to reconstruct the extensor mechanism. Reconstructive techniques include implantation of massive endoprosthesis (megaprosthesis), osteoarticular allografts (OAs), or allograft-prosthesis composites (APCs). Methods: This was a retrospective analysis of clinical data relating to patients who underwent proximal tibial arthroplasty in our regional bone tumour centre from 2010 to 2018. Results: A total of 76 patients fulfilled the inclusion criteria and were included in the study. Mean age at surgery was 43.2 years (12 to 86 (SD 21)). The mean follow-up period was 60.1 months (5.4 to 353). In total 21 failures were identified, giving an overall failure rate of 27.6%. Prosthesis survival at five years was 75.5%, and at ten years was 59%. At last follow-up, mean knee flexion was 89.8° (SD 36°) with a mean extensor lag of 18.1° (SD 24°). In univariate analysis, factors associated with better survival of the prosthesis were a malignant or metastatic cancer diagnosis (versus benign), with a five- and ten-year survival of 78.9% and 65.7% versus 37.5% (p = 0.045), while in-hospital length of stay longer than nine days was also associated with better prognosis with five- and ten-year survival rates at 84% and 84% versus 60% and 16% (p < 0.001). In multivariate analysis, only in-hospital length of stay was associated with longer survival (hazard ratio (HR) 0.23, 95% confidence interval (CI) 0.08 to 0.66). Conclusion: We have shown that proximal tibial arthroplasty with endoprosthesis is a safe and reliable method for reconstruction in patients treated for orthopaedic oncological conditions. Either modular or custom implants in this series performed well. Cite this article: Bone Jt Open  2022;3(9):733–740.